Effect of the Location of Strut Chordae Insertion on Computational Modeling and Biomechanical Evaluation of Mitral Valve Dynamics - Woojae Hong; Soohwan Jeong; Minsung Ko; Hyun Hak Kim; Hyunggun Kim (Applied Sciences, 2021)
The strut chordae (SC) have a unique structure and play an important role in reinforcing the tunnel-shaped configuration of the mitral valve (MV) at the inflow and outflow tracts. We investigated the effect of varying the SC insertion location on normal MV function and dynamics to better understand the complex MV structures. A virtual parametric MV model was designed to replicate a normal human MV, and a total of nine MV modes were created from combinations of apical and lateral displacements of the SC insertion location. MV function throughout the full cardiac cycle was simulated using dynamic finite element analysis for all MV models. While the leaflet stress distribution and coaptation showed similar patterns in all nine MV models, the maximum leaflet stress values increased in proportion to the width of the SC insertion locations. A narrower SC insertion location resulted in a longer coaptation length and a smaller anterior coaptation angle. The top-narrow MV model demonstrated the shortest anterior leaflet bulging distance, lower stresses across the anterior leaflet, and the lowest maximum stresses. This biomechanical evaluation strategy can help us better understand the effect of the SC insertion locations on mechanism, function, and pathophysiology of the MV.